Pemanfaatan Aplikasi Game Teka-Teki Silang sebagai Media Pembelajaran untuk Peningkatan Keterlibatan dan Pemahaman Peserta Didik - Navisa Navisa; Siti Halima Sineri; Rahma Nur Khalifah3; Halimatus Sadiyah; Salza Putri Amelia Jaidi; Tahta Faddel Faddilah; Ika Putra Viratama (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to describe the use of the Crossword Puzzle Game Application (TTS) as a learning medium to increase students' involvement and understanding in the learning process. The rapid development of technology demands educational innovation, and gamification, especially in the form of mobile TTS game applications, offers attractive and accessible solutions. Using qualitative research methods with a phenomenological approach, data was collected through in-depth interviews, observations, and document analysis from selected groups of students and teachers who had used the application. The results of the study show that this application effectively increases the motivation, activeness, and vocabulary memory of students. In addition, TTS games provide challenges that spark curiosity and encourage collaboration between learners while solving puzzles. The app also provides a fun, interactive, and adaptive learning environment to individual learning needs, moving away from traditional methods that tend to be monotonous. This study concludes that the TTS Game Application is a very effective, interesting, and relevant educational tool for modern learners and has the potential to be applied to a wide range of subjects.